Development of a typical algorithm for renovation of industrial complexes - S. N. Kutenev (Вестник Северо-Кавказского федерального университета)
The current economic situation in the country and the world considerably influences all spheres of economic activity of enterprises. The impact of the external environment obliges the organizations in particular and the economics of the regions in general to be flexible, highly adaptive. Extensive development no longer brings requirable results and more often intensive way of development with usage of ESG principles seems appropriate when it comes to building management systems. But the intensification of production activity is based on tools of production: fixed assets and production infrastructure. In this regard, the renovation of existing industrial complexes that do not meet the requirements of the external environment is considered relevant.